Analysis of orthogonal plates by the theory of equivalences - Yen, Nguyen Manh (Vietnam Journal of Mechanics, 1981)
The Prineiple of the Theory of Equivalences is to replace the Solid Body by a Fictions body which is easier to calculale. Using an Equivalent Solid made up of Bars with Geometrical and mechanical properties, the Problem of the Orthogonal Plates is then replaced by a Problem of research of the internal force state in a structure Using method of deformation. The computer program intended for Minsk- 32 is segmented in two parts utilizing only internal Memory.